Prevalence of stress and associated factors among students in Ethiopia: a systematic review and meta-analysis - Bezie, Anmut Endalkachew; Abere, Giziew; Zewude, Girum Tareke; Desye, Belay; Daba, Chala; Abeje, Eyob Tilahun; Keleb, Awoke (Frontiers in Public Health, 2025)
IntroductionStress is an increasing public health issue among the student population. This stress affects their academic performance, mental health, and overall well-being. As a result, we conducted a systematic review and meta-analysis to determine the pooled prevalence and associated factors of stress among students in Ethiopia.MethodsAn extensive search of electronic databases such as PubMed, Google Scholar, Semantic Scholar, HINARI, and Science Direct, cross-referencing, and Google manual search was conducted to identify cross-sectional studies published from 1998 to 2024. The preferred PRISMA guideline was used to report items for this systematic review and meta-analysis. To extract data, Microsoft Excel 16 and to analyze STATA 17 software were used. The JBI quality assessment tool was used for the included studies with medium to high-quality scores. To estimate the pooled prevalence of stress and its associated factors, a random effects model was used. The funnel plot and Egger’s regression test were used to assess publication bias, and I2 test statistics were used to determine heterogeneity of the included studies. The protocol for this review has been registered with PROSPERO (ID: CRD42024578490).ResultsA total of 23 studies with 8,946 study participants met the inclusion criteria. The pooled prevalence of stress among students in Ethiopia was 37.64% (95% CI: 29.61–45.66; I2 = 98.8%). Female gender (OR = 1.82, 95% CI: 1.57–2.12), rural resident (OR = 1.51, 95% CI: 1.22–1.87), living outside university dormitory (OR = 2.02, 95% CI: 1.34–3.05), the habit of alcohol consumption (OR = 1.46, 95% CI: 1.12–1.91), being a cigarette smoker (OR = 2.36, 95% CI: 1.49–3.74), being a khat chewer (OR = 1.35, 95% CI: 1.02–1.80), working in an unfavorable environment (OR = 1.80, 95% CI: 1.20–2.71), and having poor social support (OR = 1.93, 95% CI: 1.39–2.68), were significantly associated with an increased risk of stress.ConclusionThe findings of this systematic review and meta-analysis indicated a high prevalence of stress among students. The study identified female gender, being a rural residence, living outside a university dormitory, khat chewing, having the habit of alcohol consumption, working in an unfavorable environment, poor social support, and cigarette smoking as significant risk factors for stress. To develop coping skills and resilience, integrating mental health education into the curriculum could help students to prevent stress. Furthermore, strategies such as academic support programs, substance use reduction programs, counseling services, and stress management workshops could be beneficial.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024578490, CRD42024578490.